A DFT study of Pt layer deposition on catalyst supports of titanium oxide, nitride and carbide. Issue 48 (24th November 2015) - Xia, Xin; Jones, Glenn; Sarwar, Misbah; Tang, Qian; Harkness, Ian; Thompsett, David
Abstract : Due to carbon corrosion under the electrochemical conditions in PEMFCs, alternative ceramic supports to carbon such as TiO2 have been considered to improve the environmental resistance and catalyst durability. Abstract : Due to carbon corrosion under the electrochemical conditions in PEMFCs, alternative ceramic supports to carbon such as TiO2 have been considered to improve the environmental resistance and catalyst durability. In this work, a series of metal oxides MO2 (M = Ti, Ir, Ru), doped and reduced TiO2 surfaces, titanium nitride and carbide ceramic supports have been chosen to study the Pt deposition behavior using density functional theory. The stacking orders and the electronic screening effect of Pt deposition layers on the different geometric structures of the support surfaces are discussed based on a simple periodic slab model. The structural stability and wetting tendency of Pt overlayers have been estimated via energetic descriptors. The interfacial bonding of catalyst-support has been investigated through the electron density analysis for a group of Ti containing substrates. This suggests a reduced Ti charge state as well as a stronger covalent character of the support material, facilitating Pt bonding.